Exploring Translation Profession in Iraq: A sociological Perspective - Al-danani, Mansour (Technium Social Sciences Journal, 2024)
The motivation for the current study is two-pronged. First, it tries to address the existent obstacles for establishing a translation profession in Iraq; second, on the light of the recommendations suggested by the active agents in the field, the study seeks to come up with some solutions and suggestions to upgrade the status quo. The key agents such as translators, publishers and others, and in addition to the institutions involved have all been the recent emerging research focus in translation studies. Looked at as a profession, the research avenues have been to investigate the status of translation from a sociological perspective. For this purpose, in-depth interviews conducted with a sample of translation agents in Basra city to collect data qualitatively in Iraq. The study reached some significant results that indicate the challenges facing the establishment of translation as a profession in Iraq. Based on the participated interviewees’ comments and replies, and the reviewed relevant literature, some solutions and suggestions were introduced to help improve the current situation